Targeted drug delivery using polymeric nanoparticles for the treatment of cancer: a review - Penheiro, Diandra Elizabeth (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.